Rightful heritage : Franklin D. Roosevelt and the land of America - Brinkley, Douglas (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2016)
Examines the environmental legacy of Franklin Roosevelt and the New Deal, evaluating the creation of the Civilian Conservation Corps and the dozens of state park systems that were protected by his decisions.
Keywords: Roosevelt, Franklin D. -- 1882-1945; Roosevelt, Franklin D. -- 1882-1945; Civilian Conservation Corps (U.S.); Civilian Conservation Corps (U.S.); Conservation of natural recources -- United States -- History; Nature conservation -- United States -- History; Parks -- United States -- History; Conservationists -- United States -- Biography; Presidents -- United States -- Biography; Conservation of natural recources -- United States -- History; Nature conservation -- United States -- History; Parks -- United States -- History; Conservationists -- United States -- Biography; Presidents -- United States -- Biography